The influence of preoperative serum anticholinergic activity and other risk factors for the development of postoperative cognitive dysfunction after cardiac surgery - Plaschke, Konstanze; Hauth, Steffen; Jansen, Claudia; Bruckner, Thomas; Schramm, Christoph; Karck, Matthias; Kopitz, Jürgen (The journal of thoracic and cardiovascular surgery, 2013)
Objective: Patients undergoing cardiac surgery are at risk for postoperative cognitive dysfunction (POCD). Evaluating preoperative risk factors represents 1 possible way to minimize the postoperative risk of cognitive dysfunction. We investigated marked deterioration in cholinergic neurotransmission as 1 such potential risk factor for transient and long-lasting POCD. Serum anticholinergic activity (SAA) has already been described as a risk factor for developing delirium in an elderly study population. However, the role of SAA for long-lasting POCD is unknown. Methods: Following local ethics board approval and written informed consent, we recruited a cohort of patients aged ≥ 55 years undergoing cardiac surgery. Before surgery, levels of SAA were measured and a battery of neuropsychologic tests (NPTs) was applied. S100 calcium binding protein ß concentration was measured intraoperatively. Pre-, intra-, and postoperative patient-specific characteristics were recorded. The NPTs were repeated 3 months after hospital discharge to evaluate 3-month POCD. A group of nonsurgical patients (n = 34) was recruited as control subjects to adjust NPT scores, using reliable methods for the change index. Logistic multivariate regression was used to evaluate independent predictors of POCD. Results: One hundred fifty-four patients were screened before surgery, and 117 completed the second NPT. POCD was identified in 25.6% of patients. In contrast to intraoperatively increased S100 calcium binding protein ß, preoperative SAA was not associated with POCD following adjustment for covariates. Conclusions: Preoperatively increased SAA did not predict POCD 3 months after cardiac surgery.
Available online 27 August 2012
Gesehen am 22.08.2018